Exploring the intricacies of consumer perception : the alignment of cause and strategy in corporate social responsibility - Reimann, Leonie Carlotta (2024)
The purpose of this study is to test the intricacies of consumer sensitivity to the alignment or misalignment of a company's Corporate Social Responsibility (CSR) strategy with its environmental impact and how this affects consumer perceptions and behavior in terms of brand attitude, consumer trust and purchase intention. The research was carried out on the example of Coca-Cola. Amidst increasing consumer awareness of corporate ethics and environmental impact, this research adopts a quantitative approach, utilizing an online survey. Respondents were grouped into control, aligned, and misaligned categories exposing them to Coca-Cola CSR initiatives. The study revealed an improvement in brand attitude among consumers exposed to misaligned CSR information, suggesting that consumers respond more leniently to the complexity of CSR communications than anticipated. Consumer trust appeared robust against CSR misalignment, implying that deep-rooted brand relationships overshadow CSR messaging. Engagement in CSR was perceived positively, highlighting a general appreciation for CSR efforts over strategic fit. Interestingly, inconsistencies between Coca-Cola's environmental impact and CSR activities did not significantly impact purchase intentions, implying that brand loyalty or product satisfaction may have a stronger influence on purchasing decisions. The study suggests that consumers integrate CSR misalignments within a broader brand perception context. Limitations were sample representativeness and the challenge of separating CSR impact from existing brand perceptions, highlighting the complexity of consumer reactions to CSR. The findings underline the need for a comprehensive CSR strategy, communication approach, and its effect on consumer behavior.